2019
DOI: 10.1055/s-0039-1692207
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Nonketotic Hyperglycinemia in Lebanon: 14-Year Retrospective Review

Abstract: Nonketotic hyperglycinemia is a rare inborn error of glycine metabolism characterized by a severe metabolic encephalopathy with drug-resistant seizures. Here, we report the outcome of nonketotic hyperglycinemia in a cohort of patients diagnosed and followed-up at a tertiary care reference center in Lebanon, between 2000 and 2014.Eight out of 12 patients with nonketotic hyperglycinemia were retrospectively reviewed. The remainders were excluded for incomplete data. The majority of cases presented with seizures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…Standard treatment strategies include the reduction of the plasma concentration of glycine, the use of N-methyl-D-aspartate (NMDA) receptor site antagonists, and the symptomatic care to control intractable seizures in addition to antiepileptic drugs. 7 The current study presented a new case of NKH.…”
Section: Introductionmentioning
confidence: 78%
“…Standard treatment strategies include the reduction of the plasma concentration of glycine, the use of N-methyl-D-aspartate (NMDA) receptor site antagonists, and the symptomatic care to control intractable seizures in addition to antiepileptic drugs. 7 The current study presented a new case of NKH.…”
Section: Introductionmentioning
confidence: 78%
“…Attempts to use the above-mentioned therapy resulted in a different clinical response in patients or a complete lack of response, which raises doubts as to the validity of the therapy. In some patients with the classical variant of NKH, no clinical improvement was observed despite the early use of sodium benzoate and/or dextromethorphan, even if a reduction in glycine plasma concentration was temporarily achieved [ 3 , 16 , 17 ]. The wide variation in therapeutic effects may be influenced by the heterogeneity of NKH-inducing mutations, which has not always been considered [ 8 ].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Similarly, Kava et al achieved a significant reduction in seizure frequency and in antiepileptic drug use in a patient with epileptic encephalopathy with several seizure types, including flexor spasms, multifocal clonic and myoclonic seizures [ 26 ]. In addition, lowering glycine levels, improving tonic spasm and tonic-clonic seizure control and complete resolution of tonic-clonic seizures when the KD was used were also reported [ 3 ]. It has been shown that the use of this diet can bring benefits even in NKH patients with very severe forms of seizures, including the resolution of super-refractory status epilepticus (SRSE) [ 42 ].…”
Section: Nonpharmacological Treatment Of Epileptic Seizuresmentioning
confidence: 99%
See 2 more Smart Citations